Elements of Large Scale Mathematical Programming Part II: Synthesis of Algorithms and Bibliography - Geoffrion, Arthur M. (Management Science, 1970)
The problem manipulations and solution strategies of Part I of this paper are now further illustrated by combining them in various ways to yield several known algorithms. The main object is not an exposition of these algorithms, although this is certainly important; rather, we wish to focus on the principal patterns in which manipulations and strategies can be assembled. These patterns constitute the real common denominators in the literature on large-scale programming. See Table 2 in Part I.